Mixed marriages and Jewish identity in Philo’s Alexandria (Iter, 2022)
In his treatise O n the sp e c ia l laws 3, Philo of Alexandria organizes and explainsthe biblical laws about marriage and sexuality and includes among them one whichprohibits Jews to marry “a person from another nation” (aXXo£0v£i) (Spec. 3.29).Since this absolute interdiction lacks a specific source in the Pentateuch, our studyaims to inquire the reasons why Philo assumes such an adverse posture towardsmixed marriages. With this goal, we will analyze, in the first place, the passagesfrom the Torah which could have functioned as an exegetical basis -Dt 7.3-4, Ex34.16, Dt 23.4- even though none of them reaches the universality that Philo assignsto the prohibition. In the second place, we will examine other passages of Philoswork in which he manifests his attitude towards mixed marriages; in particular, hisinterpretation of biblical stories about unions between Hebrews and foreign slaves,such as those of Abraham with Hagar (O n A b r a h am 250-254) and of Jacob with Leahand Rachel (O n v ir tu e s 223-225), among others. By means of this analysis, we willtry to demonstrate the hypothesis that Philos position towards mixed marriages isconnected with the unstable socio-political condition of the Jewish community' inthe city of Alexandria under the rule of the Roman Empire, at the same time that itreceives a strong influence from Greek and Roman legal statutes for the transmissionof citizenship.
Keywords: Philo - Alexandria - mixed marriages - Jewish identity - Roman Empire